A microstructural investigation of a Na2SO4 activated cement-slag blend. (December 2021) - Fu, Jiayi; Bligh, Mark W.; Shikhov, Igor; Jones, Adele M.; Holt, Camille; Keyte, Louise M.; Moghaddam, Farzad; Arns, Christoph H.; Foster, Stephen J.; Waite, T. David
Abstract: The reactivity and early strength of cement:slag binders is usefully enhanced by the addition of sodium sulfate though the underlying mechanisms of the relationship between the enhanced hydration reactions and the structural aspects of the strength behavior remain unclear. In this study, microstructural development in the presence of Na2 SO4 was investigated utilizing mercury intrusion porosimetry (MIP), NMR relaxometry, and XRD. Increased rates of early strength development and decreased rates of late strength development due to the presence of added Na2 SO4 were linked to effects on capillary porosity refinement. While degree of hydration at later age was shown to have been lower in the presence of Na2 SO4, and may have been responsible for the higher capillary porosity, a clear alteration in the pathway of microstructural development had occurred with inhibition to hydration of the slag component due to earlier microstructural development proposed.